THE ROLE AND IMPORTANCE OF ATTRACTIVE RELATIONSHIPS IN THE DEVELOPMENT OF CHILDREN OF PRESCHOOL AGE - Shodiyev Rizamat Davronovich; Uzoqov Muxriddin Faxriddin ogli (Scholar Express Journal, 2022)
Attractive attitude in education is one of the humane principles of pedagogy. The article analyzes the emergence of an attractive attitude and its features of application in the preschool education system at the present stage
Keywords: attractive; attitude; approach; principle